Nurse managers’ perspectives on nurses’ performance in mentorship program - Aung, Khin Thandar; Jamal, Nor Qurratul Ain (2016)
Mostly, nurses are dealing with different challenges in the everyday working environment due to always changing and the development of new technology and treatment. Nevertheless, it is more stressful and challenging for newly graduated nurses while adapting the new environment at the time of first posting. This situation reflects the high turnover rate and job dissatisfaction among new nurses. Therefore, a mentorship program was introduced to provide guidance, support and advice to them. The aim of this study was to explore the nurse managers’ perspectives on nurses’ performance in a mentorship program. A cross-sectional survey was conducted on 51 nurse managers in Hospital TengkuAmpuanAfzan (HTAA), Kuantan, Pahang, by using modified and self-developed questionnaire with the Cronbach’salpha value 0.994. The data were analysed by using SPSS, version 19. The gender of respondents were predominantly female (100%). The mean age is 45.41 (SD ± 4.51). In terms of level of education, the majority of the respondents (76.5%) was having a diploma. The majority have been in practice as a staff nurse between 11 to 20 years, and most of them have been practicing as nurse managers for about five years and less. Meanwhile, results showed that the nurse managers’ had positive perceptions upon newly graduated nurses’ performance in the mentorship program, concerning on their effective communication, professional development and creative thinking. As a conclusion, it is vital to identify the effectiveness of the mentorship program among nurses; hence, it enhances job satisfaction among new nurses.